A model of collaboration between nursing education institutions in the North West Province of South Africa - Kathleen K. Direko; Mashudu Davhana-Maselesele (AOSIS, 2017)
Background: Professional nursing in South Africa is obtained through a 4-year diploma offered at nursing colleges, or a 4-year degree in universities, and the South African Nursing Council (SANC) registered both for professional nursing. New SANC legislation now requires a bachelor's degree for registration as professional nurse. Objectives: The aim of the study was to explore and describe perceptions of nurse educators and stakeholders to develop a model of collaboration for joint education and training of nursing professionals by colleges and universities through a bachelor's degree. Method: A mixed methods approach was used to explore perceptions of nurse educators utilising a questionnaire, and perceptions of other nurse training stakeholders through interviews, about a model of collaboration between the college and the university. Results: Themes that emerged from the interviews included identifying collaboration goals, establishing a conducive environment, maximising exchange of resources, role clarification and perceived challenges. Quantitative results showed high agreement percentages (84.13%-100%) on most basic concepts and themes. A model of collaboration was developed indicating a framework, agents, recipients, procedure, dynamics, and terminus. Conclusion: A model of collaboration was acceptable to the majority of nurse education stakeholders. Other implications are that there was a need for the improvement of scholarship among nurse educators and clinical mentors, sharing rare skills, and addressing perceived challenges.